2017
DOI: 10.2147/ndt.s127094
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a single salvianolic acid A treatment on photothrombosis-induced sustained spatial memory impairments

Abstract: With respect to the high burden of ischemic stroke and the absence of pharmacological treatment for promoting rehabilitation, promising candidates with specific effects on long-term functional recovery are highly desired. Candidates need reasonable experimental paradigms to evaluate the long-term functional outcome focused on ischemia-induced sensorimotor and memory deficits. “Danshen”, a traditional Chinese herb, has long been used to treat coronary and cerebral vascular diseases as well as dementia. Salviano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Third, the damage induced by ischemia shows a developing process that it enables us to test the impact of different levels of damage on contextual fear memory, which is ignored in the previous ( Felberg et al, 2000 ). This model could be also applied to study the mechanism of ischemia induced amnesia and the efficacy of neuroprotective drugs ( Esiri et al, 1999 ; Yu et al, 2015 ; Jiao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the damage induced by ischemia shows a developing process that it enables us to test the impact of different levels of damage on contextual fear memory, which is ignored in the previous ( Felberg et al, 2000 ). This model could be also applied to study the mechanism of ischemia induced amnesia and the efficacy of neuroprotective drugs ( Esiri et al, 1999 ; Yu et al, 2015 ; Jiao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, for other purposes, the researchers need to adjust the related parameters including the laser power and the location of the optical-fiber tips to reduce the potential damage at adjacent areas. Meanwhile, it was worthwhile to note that the Nissl staining or immunofluorescence is much greater in the high-magnification image than TTC staining ( Jiao et al, 2017 ). We still applied the TTC staining for most experiments because the Nissl staining was not sensitive at the early stage of ischemia, and the tissues were two fragile during 50-μm slice preparation especially for the animals with 24-h injury at the amygdala, and the TTC staining was the good selection for the brain slices that already were applied to the electrophysiological recording.…”
Section: Discussionmentioning
confidence: 99%
“…SAA can significantly reduce the cerebral infarct area and brain water content of tMCAO rats, reduce neurological deficits and pathological changes, and enhance the anti-inflammatory and antioxidant capacities of tMCAO rats [89]. SAA was shown to improve the sensorimotor and persistent memory impairments caused by focal ischemia in the unilateral frontal cortex of rats, suggesting that SAA has therapeutic potential in the treatment of IS-related memory impairment [90]. In addition, SAA can inhibit the production of ONOO-, up-regulate the phosphorylation levels of protein kinase B (AKT), forkhead transcription factor (FKHR) and extracellular signal-regulated kinase (ERK), increase glucose metabolism after cerebral ischemia, reduce neurological deficits, and protect the brain from ischemia/reperfusion injury [91].…”
Section: Other Phenolsmentioning
confidence: 95%
“…16 Finally, many studies that make no mention of cleaning whatsoever. 12,14,17,22 The goal of this study was to determine whether the cleaning of EPM apparatus affects animal performance, because few data in this field are available. One study in mice showed decreased anxiety and neophobia in a light:dark test when tested on a soiled apparatus as compared with a clean device.…”
mentioning
confidence: 99%